Modern systems analysis and design - Valacich, Joseph S. 1959-; George, Joey F. (Pearson Education Limited, 2017)
For Structured Systems Analysis and Design courses. Help Students Become Effective Systems Analysts Using a professionally-oriented approach, Modern Systems Analysis and Design covers the concepts, skills, and techniques essential for systems analysts to successfully develop information systems. The Eighth Edition examines the role, responsibilities, and mindset of systems analysts and project managers. It also looks at the methods and principles of systems development, including the systems development life cycle (SDLC) tool as a strong conceptual and systematic framework. Valuing the practical over the technical, the authors have developed a text that prepares students to become effective systems analysts in the field